MEMBACA ULANG PEMIKIRAN GANDHI TENTANG KEMANUSIAAN - I Ketut Wisarja; I Ketut Sudarsana (Jurnal Ilmu Sosial dan Humaniora, 2018)
Mohandas Karamchand Gandhi is a humanist fighter from India. The struggles of his life both in India and in South Africa have prompted him to become a humanitarian fighter with the "Nonviolent Movement". Gandhi, even though his people were gone hundreds of years ago, but his thoughts still leave interesting things to be studied in the present masses and in the upcoming masses. Gandhi's thoughts about humanity are profound and utopian, so they still have the appeal to be studied by the persecutors and observers of nonviolence. Every move Gandhi struggle always stressed the importance of respecting humanity, because humans can develop themselves and foster unity throughout the world with love. The ability to love enables human beings to change, evolves toward improvement and perfection. Gandhi's humanitarian thoughts, then branched out by seeing British atrocities in India, especially the "Amritsar Massacre" and other atrocities in Punyab by British colonials, brought him into the realm of politics he did not really want. Gandhi's efforts against British rule did not mean the destruction of the English, but a movement against the practice of colonialism with the movements of ahimsa, satyagraha, swadesi, and hartal (civil-disobedience, noncooperation and fasting). It means that Gandhi's struggle against the British colonial remains on the respect and respect of humanity, the enemy must be defeated not by humiliation, but by uplifting.